Requirements of health policy and services journals for authors to disclose financial and non-financial conflicts of interest: a cross-sectional study - Assem M. Khamis; Maram B. Hakoum; Lama Bou-Karroum; Joseph R. Habib; Ahmed Ali; Gordon Guyatt; Fadi El-Jardali; Elie A. Akl (BMC, 2017)
Abstract Background The requirements of the health policy and services journals for authors to report their financial and non-financial conflicts of interest (COI) are unclear. The present article aims to assess the requirements of health policy and services journals for authors to disclose their financial and non-financial COIs. Methods This is a cross-sectional study of journals listed by the Web of Science under the category of 'Health Policy and Services'. We reviewed the 'Instructions for Authors' on the journals' websites and then simulated the submission of a manuscript to obtain any additional relevant information made available during that step. We abstracted data in duplicate and independently using a standardised form. Results Out of 72 eligible journals, 67 (93%) had a COI policy. A minority of policies described how the disclosed COIs of authors would impact the editorial process (34%). None of the policies had clear-cut criteria for rejection based on the content of the disclosure. Approximately a fifth of policies (21%) explicitly stated that inaccurate or incomplete disclosures might lead to manuscript rejection or retraction. No policy described whether the journal would verify the accuracy or completeness of authors' disclosed COIs. Most journals' policies (93%) required the disclosure of at least one form of financial COI. While the majority asked for specification of source of payment (71%), a minority asked for the amount (18%). Overall, 81% of policies explicitly required disclosure of non-financial COIs. Conclusion A majority of health policy and services journal policies required the disclosure of authors' financial and non-financial COIs, but few required details on disclosed COIs. Health policy journals should provide specific definitions and instructions for disclosing non-financial COIs. A framework providing clear typology and operational definitions of the different types of COIs will facilitate both their disclosure by authors and reviewers and their assessment and management by the editorial team and the readers.